Strategies to facilitate safe sexual practices in adolescents through integrated health systems in selected districts of Zimbabwe: a mixed method study protocol - Wilfred Njabulo Nunu; Lufuno Makhado; Jabu Tsakani Mabunda; Rachel Tsakani Lebese (BMC, 2020)
Abstract Background Zimbabwe has the highest teenage pregnancy rate in Sub Saharan Africa. Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) prevalence in adolescents that are from tribes that perform cultural initiations and subscribe to certain norms are higher than the national prevalence which is estimated at 12% (18 and 13.6% respectively) in Zimbabwe. Indigenous Health Systems (IHSs) and Modern Health Systems (MHSs) in Zimbabwe run parallel thereby introducing challenges in the management of adolescent sexual health due to conflicts. This study seeks to develop strategies that will facilitate the integration of IHSs and MHS in Mberengwa and Umguza districts. Methods This research will be conducted in two phases. The first phase would utilise a concurrent triangulation mixed methods design with both qualitative and quantitative approaches. The findings from the qualitative and quantitative approaches would be merged through a comparison of findings side by side. The second phase would focus on the development and validation of strategies that would facilitate the integration of IHSs and MHSs. The Strength, Weakness, Opportunity and Threat (SWOT) analysis would be applied on interfaced findings from phase one. The Basic Logic and the Build, Overcome, Explore and Minimise (BOEM) models would then be used to develop strategies based on the SWOT findings. The developed strategies would be validated through the application of Delphi technique and administration of checklist to selected key stakeholders through organised workshops. Discussion There have been no known studies found in the literature that explores the possibility and developed strategies of integrating IHSs and MHSs so as to promote safe sexual practices in adolescents. Most programs on sexual health have ignored the role of IHSs and MHSs in influencing safe sexual practices leading to them failing to attain desired goals. A lot of emphases has been targeted at minimising the spread of Sexually Transmitted Infections (STIs) through advocating for utilisation MHSs rather than focussing on an integrating systems that are meant to manage Adolescent Sexual Health (ASH) related issues. The study protocol was approved by the University of Venda Ethics Committee Registration (SHS/19/PH/17/2608) on the 26th of August 2019.